A Convenient Approach to N‐(Di‐tert‐butylphosphanyl)‐ and N‐(Di‐tert‐butylphosphoroselenoyl)formamidinium Salts: Carbene Precursors. Issue 7 (23rd January 2014) - Marchenko, Anatoliy; Koidan, Georgyi; Hurieva, Anastasiya; Savateev, Aleksandr; Rozhenko, Alexander B.; Sotiropoulos, Jean‐Marc; Shishkina, Svitlana V.; Shishkin, Oleg V.; Kostyuk, Aleksandr
Abstract: The reactions of (di‐ tert ‐butylphosphanyl)amines and P, P ‐di‐ tert ‐butylphosphinoselenoic amides with Alder's dimer were studied. For di‐ tert ‐butylphosphanylamines, the reaction proceeds by primary electrophilic attack of Alder's dimer at the phosphorus atom to afford a dicationic salt3 . The deprotonation of3 led to N ‐phosphanylformamidine5 ("phosfam"). Alkyl(di‐ tert ‐butylphosphanyl)amines reacted with Alder's dimer in a 2:1 molar ratio to give N ‐phosphanylformamidinium salts; the second equivalent of (alkylamino)phosphane acts as a base. (Arylamino)phosphanes reacted with Alder's dimer to give benzazaphospholium derivatives. To direct the electrophilic attack of Alder's dimer at the nitrogen atom, phosphinoselenoic amides were used. They reacted with Alder's dimer at the selenium atom followed by a selenium–phosphorus shift to give N ‐(di‐ tert ‐butylphosphoroselenoyl)formamidinium salts. The phosphinoselenoic amides with bulky substituents (adamantyl, t Bu) underwent cleavage of the N–alkyl bond to afford phosfams. Various key intermediates such as3 and22b were isolated and characterized. A convenient method for the synthesis of carbene precursor P III and P V N ‐substituted formamidinium salts was developed. Abstract : Carbene precursor P III and P V N ‐substituted formamidinium salts are obtained by the reaction of (di‐ tert ‐butylphosphanyl)amines and P, P ‐di‐ tert ‐butylphosphinoselenoic amides with Alder's dimer. The primary electrophilic attack of Alder's dimer proceeds at the phosphorus atom of the phosphanylamines or at the selenium atom of the phosphinoselenoic amides.